Acoustic radiation force impulse tissue characterization of the anterior talofibular ligament: a promising noninvasive approach in ankle imaging. Issue 4 (2nd October 2018) - Hotfiel, Thilo; Heiss, Rafael; Janka, Rolf; Forst, Raimund; Raithel, Martin; Lutter, Christoph; Gelse, Kolja; Pachowsky, Milena; Golditz, Tobias
ABSTRACT: Objectives : The anterior talofibular ligament (ATFL) is the most frequently injured ligament during inversion strains of the ankle. The purpose of this study was to evaluate the feasibility of acoustic radiation force impulse (ARFI) elastography and to determine the in vivo mechanical properties of the ATFL in healthy athletes. Methods : Sixty healthy athletes (32 female, 28 male; 28.9 ± 2.1 years) were recruited from the medical and sports faculty. ARFI values, represented as shear wave velocities (SWVs) as well as conventional ultrasound were obtained for the ATFL in neutral ankle position. A clinical assessment was performed in which the American Orthopaedic Foot & Ankle Society (AOFAS) Ankle-Hindfoot Score and the functional ankle ability measure (FAAM) were collected. Interobserver and intraobserver reliability (repeated sessions and repeated days) were assessed using an intra class correlation coefficient (ICC) and typical error (TE) calculation in absolute (TE) and relative units as coefficient of the variation (CV). Results : SWV values of the ATFL had an average velocity of 1.79 ± 0.20 m/s for all participants, with an average of 1.72 ± 0.36 m/s for females and 1.85 ± 0.31 m/s for males. The interobserver and intraobserver reliability revealed an ICC of 0.902 and 0.933 (TE of 0.67 (CV: 5.2%) and 0.52 (CV: 3.84%)), respectively. FAAM and AOFAS revealed the best possible scores. Conclusion : ARFI seems to be a valuable diagnostic modality and represents a promising imaging marker for the assessment and monitoring of ankle ligaments in the context of acute and chronic ankle instabilities; ARFI could also be used to investigate loading or sport dependent adaptions.